Triphenylamine-based fluorophores bearing peripheral diazine regioisomers. Synthesis, characterization, photophysics and two-photon absorption - Klikar, Milan; Georgiou, Dimitris; Polyzos, Ioannis; Fakis, Mihalis; Růžičková, Zdeňka; Pytela, Oldřich; Bureš, Filip (Elsevier Science, 2022)
A series of six tripodal push-pull fluorophores with D-(pi-A3) arrangement has been designed and synthesized. The structure of these fluorophores consists of a central electron-donating triphenylamine core and peripheral electron-withdrawing diazine units (pyridazine, pyrimidine, and pyrazine moieties), which are linked by an ethynylene pi-spacer. The preparation of the fluorophores involves threefold Sonogashira cross-coupling reaction starting from the key tris(4-ethynylphenyl)amine intermediate. The structure and spatial arrangement of two fluorophores were completely confirmed by X-ray analysis. Thermal and electrochemical behavior of prepared fluorophores were investigated by differential scanning calorimetry and cyclic voltammetry. Their linear optical properties were examined by UV-Vis absorption, steady-state and time resolved fluorescent spectroscopy while 2 PA analysis was used for a study of the nonlinear optical response. Experimental data were supported by DFT calculations. Based on the experimental as well as theoretical data, structure-property relationships have been thoroughly revealed.
Trifenylaminové fluorofory nesoucí koncové diaziny. Syntéza, charakterizace, fotofyzikální vlastnosti a dvoufotonová absorpce
Keywords: triphenylamine; pyridazine; pyrimidine; pyrazine; diazines; regioisomers; tripodal fluorophores; two-photon absorption; trifenylamin; pyridazin; pyrimidin; pyrazin; regioizomery; tripodální fluorofory; dvoufotonová absorpce